The IMPLEMENTATION OF MOBILE-CLOUD TECHNOLOGY IN THE PLANTATION INDUSTRY (CASE STUDY: CASSAVA PLANTATION AT PT SENTOSA GROUP) - Puad, Lailyn; Limia Budiarti, Rike; Elzas, Elzas (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2024)
Cloud Technology is increasingly becoming a prime choice among technology enthusiasts. This is due to its wide reach, security system, and relatively affordable maintenance costs. PT Sentosa Group, a long-established company that is aware of technological advancements, operates in the plantation sector and aims to develop a website capable of accommodating extensive data integration needs. A mobile application is one of the expected outcomes that can provide convenience to the company. By applying the right research methods, this initiative is expected to be completed within a short period with optimal efficiency. The use of cloud technology in this company is not new; previously, a system was already in place to manage inventory and logistics. However, with its implementation, this application can now be fully utilized by all plantation stakeholders.